Bibliometric Analysis of Research on Diesel Pollution in Antarctica and a Review on Remediation Techniques - Zheng Syuen Lim; Rasidnie Razin Wong; Chiew-Yen Wong; Azham Zulkharnain; Noor Azmi Shaharuddin; Siti Aqlima Ahmad (Applied Sciences, 2021)
Diesel is a fuel commonly used in Antarctica to supply vessels and domestic applications on site. The increasing human activities in the continent consequently have generated high fuel demand, which in turn has increased the occurrence of oil pollution due to accidental events during refueling. A related study received growing interest as more detrimental effects have been reported on Antarctic ecosystems. By adopting the bibliometric analysis, the research on diesel pollution in Antarctica collected in the Scopus database was systematically analysed. An increment in annual publication growth from 1980 to 2019 was observed and two research clusters were illustrated with “hydrocarbons” as the core keyword. Several attempts have been conducted over the past decades to remove anthropogenic hydrocarbon from previous abandoned whaling sites as well as recent oil spill incidents. However, the remote and polar conditions of Antarctica constrained the installation and operation of clean-up infrastructure. This review also briefly encompasses the approaches from past to present on the management of fuel pollution in Antarctica and highlights the potential of phytoremediation as a new bioremediation prospect.